Counterfeit Integrated Circuits: Detection and Avoidance - Tehranipoor, Mark (Springer, 2015)
This timely and exhaustive study offers a much-needed examination of the scope and consequences of the electronic counterfeit trade. The authors describe a variety of shortcomings and vulnerabilities in the electronic component supply chain, which can result in counterfeit integrated circuits (ICs). Not only does this book provide an assessment of the current counterfeiting problems facing both the public and private sectors, it also offers practical, real-world solutions for combatting this substantial threat.